Genetics - P S Verma (S. Chand, 2009)
The book helps assimilate extensive information on Genetics. Besides containing the chapters on classical genetics, it also covers molecular genetics and genetic engineering. Though it has been primarily developed for B Sc (Pass and Honours) students, it can be equally useful for MSc in Zoology, Botany, Microbiology and Biotechnology and various competitive examinations. 21 new chapters including Genetic Engineering and contemporary information on Quantitative Genetics and Immunogenetics Rich pedagogy comprising figures, tables, boxes, coloured photographs, exhaustive and explanatory glossary, Multiple Choice Questions and Answers Revision questions to test students' understanding at the end of each chapter Model solved problems to show readers how to solve Genetical problems